Heritability of submaximal exercise heart rate response to exercise training is accounted for by nine SNPs - Rankinen, T.; Sung, Y. J.; Sarzynski, M. A.; Rice, T. K.; Rao, D. C.; Bouchard, C. (Journal of Applied Physiology, 2012)
Endurance training-induced changes in hemodynamic traits are heritable. However, few genes associated with heart rate training responses have been identified. The purpose of our study was to perform a genome-wide association study to uncover DNA sequence variants associated with submaximal exercise heart rate training responses in the HERITAGE Family Study. Heart rate was measured during steady-state exercise at 50 W (HR50) on 2 separate days before and after a 20-wk endurance training program in 483 white subjects from 99 families. Illumina HumanCNV370-Quad v3.0 BeadChips were genotyped using the Illumina BeadStation 500GX platform. After quality control procedures, 320,000 single-nucleotide polymorphisms (SNPs) were available for the genome-wide association study analyses, which were performed using the MERLIN software package (single-SNP analyses and conditional heritability tests) and standard regression models (multivariate analyses). The strongest associations for HR50 training response adjusted for age, sex, body mass index, and baseline HR50 were detected with SNPs at the YWHAQ locus on chromosome 2p25 (P = 8.1 × 10-7), the RBPMS locus on chromosome 8p12 (P = 3.8 × 10-6), and the CREB1 locus on chromosome 2q34 (P = 1.6 × 10-5). In addition, 37 other SNPs showed P values <9.9 × 10-5. After removal of redundant SNPs, the 10 most significant SNPs explained 35.9% of the DeltaHR50 variance in a multivariate regression model. Conditional heritability tests showed that nine of these SNPs (all intragenic) accounted for 100% of the DeltaHR50 heritability. Our results indicate that SNPs in nine genes related to cardiomyocyte and neuronal functions, as well as cardiac memory formation, fully account for the heritability of the submaximal heart rate training response.